Benford behavior and distribution in residue classes of large prime factors. Issue 2 (10th June 2023) - Pollack, Paul; Singha Roy, Akash
Abstract: We investigate the leading digit distribution of the k th largest prime factor of n (for each fixed $k=1, 2, 3, … $ ) as well as the sum of all prime factors of n . In each case, we find that the leading digits are distributed according to Benford's law. Moreover, Benford behavior emerges simultaneously with equidistribution in arithmetic progressions uniformly to small moduli.